Literature Study on Spiritual Leadership, Organizational Citizenship Behavior (OCB) and Pandita Buddhayana's Organizational Commitment - Fisaka Prima Dianti; Budi Utomo; Tjhia Khie Khiong (Journal of Education Technology Information Social Sciences and Health, 2024)
Pandita Buddha is an individual who has a deep understanding of Dharma and has the ability to openly. Pandita Buddha plays a very significant role in the development of the Buddhist religion. Exemplary Buddhist scholars are characterized by a kind-hearted nature and behave in a way that facilitates the provision of assistance for the spiritual growth and happiness of Buddhist followers. This study aims to analyze Spiritual Leadership and Organisational Citizenship Behavior towards Organizational Commitment in the Buddhist clergy. The research method used is Systematic Literature Review (SLR) with meta-synthetic data analysis techniques. Data were obtained through a collection of journals published from 2015-2023. Based on the research findings, there are main findings indicating that spiritual leadership is positively related to OCB, showing that the dimension of spirituality in leadership can encourage positive behavior among organizational members. In addition, OCB also proves to act as a mediator between spiritual leadership and organizational commitment, emphasizing the important role of OCB in connecting leadership aspects with the individual's commitment to the organization. The practical implications of these findings include the importance of developing spiritual leadership in the organizational context to enhance the engagement and dedication of organizational members through the improvement of OCB. This study contributes to a better understanding of the complex relationship between these key variables and highlights the central role of spiritual leadership in creating a positive and committed organizational environment